On the Spectra of Commuting and Non Commuting Graph on Dihedral Group - Abdussakir, Abdussakir; Elvierayani, Rivatul Ridho; Nafisah, Muflihatun (CAUCHY, 2017)
Study about spectra of graph has became interesting work as well as study about commuting and non commuting graph of a group or a ring. But the study about spectra of commuting and non commuting graph of dihedral group has not been done yet. In this paper, we investigate adjacency spectrum, Laplacian spectrum, signless Laplacian spectrum, and detour spectrum of commuting and non commuting graph of dihedral group D2n